The genomics and epigenetics of olfactory neuroblastoma: A systematic review. Issue 4 (7th June 2021) - Kaur, Raman Preet; Izumchenko, Evgeny; Blakaj, Dukagjin M.; Mladkova, Nikol; Lechner, Matt; Beaumont, Thomas L.; Floudas, Charalampos S.; Gallia, Gary L.; London, Nyall R.
Abstract: Background: Olfactory neuroblastoma (ONB) or esthesioneuroblastoma (ENB) is a rare malignancy of the nasal cavity believed to arise from the olfactory epithelium. The goal of this study was to systematically review the genomics, epigenetics, and cytogenetics of ONB and to understand the potential clinical implications of these studies. Methods: A systematic literature review was performed for articles published before May 2020 using Cochrane, Embase, Pubmed, and Scopus databases. Inclusion criteria included genomics, cytogenetics, and epigenetics studies on ONB. Exclusion criteria included studies not in English or systematic reviews. Articles and abstracts were reviewed by two independent reviewers to reduce bias during article selection and synthesis of results. Of the 36 studies included in this review, 24 were research articles and 12 were abstracts. Results: Although recurrent mutations among ONB tumors are uncommon, alterations in TP53, DMD, PIK3CA, NF1, CDKN2A, CDKN2C, CTNNB1, EGFR, APC, cKIT, cMET, PDGFRA, CDH1, FH, SMAD4, FGFR3 and IDH2 genes have been reported in several recent studies. In addition, cytogenetic studies revealed that the landscape of chromosomal aberrations varies widely amongst ONB tumors. Conclusions: The rare character of ONB has limited the sample size available for cytogenetic, genomic, and epigenetic studies and contributes to the limitations of this systematic review. Comprehensive genomic and epigenomic studies with larger cohorts are warranted to validate the initial reports summarized in this review and to identify potential therapeutic targets for ONB.